Seasonality and distribution of cyanobacteria and microcystin toxin genes in an oligotrophic lake of Atlantic Canada. Issue 6 (7th October 2021) - Brown, Jordan; Hawkes, Kristen; Calvaruso, Rossella; Reyes‐Prieto, Adrian; Lawrence, Janice
Abstract : Cyanotoxins are an emerging threat to freshwater resources worldwide. The most frequently reported cyanotoxins are the microcystins, which threaten the health of humans, wildlife, and ecosystems. Determining the potential for microcystin production is hindered by a lack of morphological features that correlate with microcystin production. However, amplicon‐based methods permit the detection of microcystin biosynthesis genes and were employed to assess the toxin potential in Lake Utopia, NB, Canada, an oligotrophic lake that occasionally experiences cyanobacteria blooms. Samples collected at 2 week intervals from June 27th to September 27th, 2016, were screened by polymerase chain reaction (PCR) for the microcystin synthetase E gene ( mcyE ). The mcyE gene was present in some samples every sampling day, despite microcystin not being detected via ELISA, and was most frequently associated with the larger pore size fractions of the serially filtered samples. Further PCR surveys using primer sets to amplify genus‐specific (e.g., Microcystis, Anabaena/Dolichospermum, and Planktothrix ) mcyE fragments identified Microcystis as the only taxa in Lake Utopia with toxigenic potential. Sequencing of the 16S rRNA V3–V4 region revealed a community dominated by members of the order Synechococcales (from 38 to 96% relative abundance), but with significant presence of taxa from Cyanobacteriales including Microcystaceae and Nostocaceae. A persistent Microcystis population was detected in samples both testing positive and negative for the mcyE gene, highlighting the importance of identifying cyanotoxin production potential by gene presence and not species identity. To our knowledge, this study represents the first application of amplicon‐based approaches to studying toxic cyanobacteria in an understudied region—Atlantic Canada.